Relationship Between Gender Differences and Clinical Outcome in Patients With the Antiphospholipid Syndrome - Truglia, Simona; Capozzi, Antonella; Mancuso, Silvia; Manganelli, Valeria; Rapino, Luca; Riitano, Gloria; Recalchi, Serena; Colafrancesco, Serena; Ceccarelli, Fulvia; Garofalo, Tina; Alessandri, Cristiano; Longo, Agostina; et al. (Frontiers in Immunology, 2022)
Antiphospholipid syndrome (APS), characterized by artherial and/or venous thrombosis, pregnancy morbidity and “antiphospholipid” antibodies (aPL), is more common in women than in men, with a female to male ratio of about 3.5:1. Only few studies have investigated the clinical differences between male and female patients with APS. Therefore, this study was aimed to analyze the differences of clinical manifestations and laboratory tests, at diagnosis, between female and male APS patients and the clinical outcome. We enrolled 191 consecutive APS patients (125 with primary APS, PAPS, and 66 with secondary APS, SAPS) with a female predominant ratio of approximately 3:1 (142 vs 49). The prevalence of PAPS was higher in males than females (p<0.001). The analysis of aPL profile revealed that high IgM anti-cardiolipin (aCL) and high-medium IgG aCL titers were more frequent in males. In thrombotic APS peripheral arterial thrombosis was more common in male than female patients (p=0.049), as well as myocardial infarction (p=0.031). Multivariate analysis to correct for cardiovascular risk factors, high titer of aPLs and triple positivity for aPLs, revealed that the odds ratio for myocardial infarction in male was 3.77. Thus, APS may be considered as a disease in which serological (IgM titer) and clinical profiles are influenced by gender.